Circadian Variation in the Median Effective Dose of Epidural Ropivacaine for Labor Analgesia - Deng, Jiali; Wei, Changna; Liu, Lin; Qian, Jing; Xiao, Fei; Chen, Xinzhong (Frontiers in Medicine, 2021)
Background: We hypothesized that the dose requirement for epidural ropivacaine for labor analgesia would vary between day and night, and therefore designed a study to determine and compare the median effective dose (ED50) of ropivacaine in parturients having epidural labor analgesia during the day versus at night. METHODS: Sixty nulliparous healthy parturients were assigned to one of two groups according to the time they requested labor analgesia: Day Group (07:01 h to 19:00 h) and Night Group (19:01 h to 07:00 h). A bolus of 0.15% ropivacaine was administered epidurally and effective analgesia was defined as attainment of a VAS pain score ≤ 10 mm within 30 min. The dose of ropivacaine for the first parturient in each group was 18 mg. The dose for each subsequent parturient was varied with increments or decrements of 3 mg based on the response of the previous subject. The ED50 was calculated using up-down sequential analysis. Probit regression was used to estimate relative mean potency of ropivacaine between groups. RESULTS: The ED50 (mean [95% CI]) of ropivacaine was lower in the Day Group (17.9 [16.5 to 19.4] mg) than in the Night Group (20.9 [19.2 to 22.7] mg) (P = 0.003). The estimate of relative potency for ropivacaine for the Night Group versus the Day Group was 0.85 (95% CI: 0.56 to 0.98). CONCLUSIONS: Under the conditions of this study, the dose requirement for epidural ropivacaine for labor analgesia was approximately 15% greater during the night than during the day.